Kontribusi Epistemologi Ibnu Khaldun terhadap Kurikulum Pendidikan Agama Islam - Imroatus Sholekah; Muhammad Arif Syihabuddin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Education is an effort to acquire knowledge and bring about change through formal, non-formal, and informal learning, each with specific objectives. To achieve these educational objectives, a structured educational plan known as a curriculum is required. This study is motivated by the need to strengthen the philosophical foundation of the Islamic education curriculum in response to changes in the era, social dynamics, and the development of knowledge, by examining Ibn Khaldun’s epistemology and curriculum as a basis for formulating the Islamic education curriculum. This study employs a conceptual approach through library research, using Muqaddimah by Ibn Khaldun as the primary source, supported by various relevant scholarly works as secondary sources. The findings indicate that Ibn Khaldun’s epistemology and curriculum make a significant contribution to the Islamic education curriculum through the integration of revelation, reason, and experience as sources of knowledge. This contribution is reflected in his classification of religious and rational sciences, the categorization of knowledge into linguistic, traditional, and rational sciences, as well as the application of a gradual learning method (tadarruj) that is oriented toward learners’ intellectual development. These findings demonstrate that Ibn Khaldun’s thought remains relevant as a philosophical foundation for developing an Islamic education curriculum that balances cognitive, affective, and psychomotor aspects and is adaptive to the dynamics of contemporary Islamic education.   Keywords: Ibn Khaldun, Epistemology, Curriculum, Islamic Education.